2014
DOI: 10.4314/ijbcs.v7i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of toxicity of <i>Bacillus thuringiensis</i>, neem oil and methamidophos against <i>Plutella xylostella</i> L. (Lepidoptera: Plutellidae) larvae

Abstract: Diamondback moth (DBM), Plutella xylostella (L.), remains a major pest of brassica crops worldwide. Chemical control of this pest remains difficult due to the rapid development of resistance to insecticides and to their effect on natural enemies. The objective of this study was to assess the toxicity of Bacillus thuringiensis (Bt), neem oil and methamidophos on larvae of P. xylostella under laboratory conditions. Leaf-dip bioassay for DBM larvae was used to assess mortality. For each treatment, three doses (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Effects of different natural control agents (A-B) against tomato leaf miner, Tuta absoluta humidity (Khidr et al 2013). Sow and Diarra (2013) reported that Bt alone is not highly effective as a control measure of lepidopterous pests but it can help and complement integrated control measures.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of different natural control agents (A-B) against tomato leaf miner, Tuta absoluta humidity (Khidr et al 2013). Sow and Diarra (2013) reported that Bt alone is not highly effective as a control measure of lepidopterous pests but it can help and complement integrated control measures.…”
Section: Discussionmentioning
confidence: 99%
“…This population decline may be related to the formation of mature cabbages that would not be preferred as laying substrates by females. Indeed, the evolution of cabbage is inversely proportional to the glucosinolates content of the plant and this could be a factor limiting egg laying (Sow et al, 2013). These observations show that the abundance of P. xylostella depends not only on the treatment of the plots but also on the development stage of plants (Ngom et al, 2020).…”
Section: Agronomic Impact Of Treatment Effect On Cabbagementioning
confidence: 82%
“…The possibility of growing it all year round, both in dry and rainy seasons, makes it possible to fund other activities and/or other crops (AUMN, 2009). Unfortunately, this crop is very susceptible to attacks from several insects and pathogens (Sow et al, 2013;Labou et al, 2016;Labou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations